Impact of the participation of rural households in the appraisal on poor households' identification. - Yusong Liu; Linyi Zheng (PLoS ONE, 2022)
Developing countries have common goals of poverty eradication and improving people's livelihoods. As the largest developing country, China has made remarkable achievements in poverty alleviation during the 30 years of reform. Although a targeted poverty alleviation mechanism was established by the Chinese government in 2013, the identification of poor households has been an arduous journey. Based on a total of 688 samples of grassroots officials and 2,621 rural households from 69 village-level divisions in 9 provinces in China, this study conducted cross-validation on the impact of the participation of rural households in the identifying poor households that required government assistance. This was from the perspectives of grassroots officials and rural households. It was investigated whether this participation led to an anomaly between the identification of poor households and the actual situation. Empirical results show that the participation of rural households in appraisals significantly increases the probability of identifying a non-poor household as a poor household (first error) and decreases the probability of failing to identify a poor household as a poor household (second error). As the impact of the first error is greater than that of the second error, the participation of rural households in appraisals has the overall effect of increasing the incorrect registrations of poor households. These results are still valid after addressing the self-selection problem. For other developing countries to successfully apply effort into poverty alleviation, in addition to focusing on increasing farmers' participation in public affairs, they should prevent any bias that may be caused by farmers' participation in public affairs; strengthen publicity and guidance; focus on the nurture of officials; perfect top-level design; and set clearer targets for poverty alleviation policies.